Fractional Partial Differential Equations Associated with Lêvy Stable Process - Reem Abdullah Aljedhi; Adem Kılıçman (Mathematics, 2020)
In this study, we first present a time-fractional L <semantics> <mover accent="true"> e ^ </mover> </semantics> vy diffusion equation of the exponential option pricing models of European option pricing and the risk-neutral parameter. Then, we modify a particular L <semantics> <mover accent="true"> e ^ </mover> </semantics> vy-time fractional diffusion equation of European-style options. Further, we introduce a more general model based on the L <semantics> <mover accent="true"> e ^ </mover> </semantics> vy-time fractional diffusion equation and review some recent findings associated with risk-neutral free European option pricing.